Penerapan Floyd-Warshall untuk Pencarian Rute Terpendek pada Aplikasi Notifikasi Kecelakaan Lalu Lintas - Haniah Mahmudah; M. Fajar Ibrahim; Okkie Puspitorini; Ari Wijayanti; Nur Adi Siswandari (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2022)
In the case of an accident, a prompt response is needed to prevent accidents or provide assistance to traffic accident victims. Several ways can be carried out to address this problem. One of them is by developing several smartphone applications for accident detection and accident notification that provide aid in traffic accidents. The existing application to assist the victims merely presents the shortest route from the respondent to the victim’s location without any features that help the respondent find a route to the nearest hospital and police station. Therefore, this study develops a smartphone application for accident alerts for victims’ relatives and respondents, which assists in locating the victim’s position and the closest hospitals and police stations. This accident notification app for smartphones utilizes open-source software and is very scalable. The outcome of this study is an Android application capable of sending accident notification broadcasts, allowing the victim’s relatives and respondents to get accident notifications and drive to the accident place using the route given by the application. In addition, the developed app also provides information about the location of the nearest hospital and police station, allowing respondents nearby the location to help the victim promptly. The results of testing the application using the black box method on the Android platform indicated that 100% of the features of this application were running well. The shortest route with the Floyd-Warshall algorithm was 4.199 km, with no route deviations from the distance testing scenario. The average speed of notification delivery response from victims to respondents was 27.86 ms.